The pharmacokinetic-nephrotoxicity relationships of CMS and CMS-E2 from the perspective of plasma and kidney drug concentrations in rats - Chenxue Guo; Lin Xi; Xingyi Qu; Zhiwei Huang; Size Li; Wanzhen Li; Xiaofen Liu; Jing Zhang (Scientific Reports)
Abstract Nephrotoxicity has seriously affected the clinical application of colistin methanesulphonate (CMS). Colistin B methanesulphonate (CMS-E2) is a novel polymyxin developed and aimed to have lower nephrotoxicity. This study aimed to investigate the relationships between pharmacokinetics (PK) and nephrotoxicity of CMS and CMS-E2 and compare the toxicity of the two drugs in rats. Rats were treated intraperitoneally with a single dose of saline, CMS [10, 20 mg/kg of colistin base activity (CBA)], and CMS-E2 (20, 40 mg/kg CBA). An LC-MS/MS method was developed to determine plasma and renal tissue concentrations of CMS/CMS-E2 and colistin/colistin B. The severity of renal injuries was examined both biochemically and histologically. The PK-toxicodynamic (TD) model was evaluated to characterize the PK of CMS/CMS-E2 and colistin/colistin B in plasma as well as its relationship with nephrotoxicity. Creatinine (CR) and blood urea nitrogen (BUN) profiles were described using an indirect link PK-TD model, with linear-effect relationship. Both the slope between colistin or colistin B concentrations in the effect compartment and CR, BUN was significantly lower for CMS-E2 compared with CMS (CR: P = 0.027, BUN: P = 0.043). The concentrations of colistin and colistin B in kidneys were correlated with CR, BUN values, and histologic examination scores. The regression coefficient of CMS-E2 between the colistin B concentrations in renal tissues and CR, BUN values were lower, as well (CR: P = 0.003, BUN: P = 0.001). The renal injuries induced by CMS and CMS-E2 lagged behind the change of plasma colistin or colistin B concentrations and correlated to those in kidneys. CMS-E2 showed significantly lower nephrotoxicity compared to CMS in vivo.